Knowledge and Practice of Traditional Skill Technology among Hill Dalit of Kaski (A study based on Pariyars, Nepali and Bishowkarma of Kaski District) - Parajuli, Biswo Kallyan (Himalayan Journal of Sociology and Anthropology, 2012)
There is a rapid change in traditional occupation and traditional skill technology of Dalit. The study shows that knowledge of the Traditional Skill Technology among Hill Dalit of Kaski district is declining.DOI: http://dx.doi.org/10.3126/hjsa.v5i0.7037 Himalayan Journal of Sociology & Anthropology-Vol. V (2012) 19-33